A morphosyntactic analysis of the pronominal system of Southern Alta - Abreu, Marvin M. (Animo Repository, 2019)
Pronouns are one of the universal components of language and they provide information on the morphosyntactic characteristics of any languages such as Philippine languages. Past researches show various analyses on the morphosyntax of PLs, a recent typological study claims that Philippine languages (PLs) are ergative. Another study shows a similar claim; however, this study utilizes the pronominal systems of major Philippine languages and uses an ergative-absolutive framework. This research examines the pronouns of Southern Alta language. It aims to contribute in the typological studies of pronominal systems of Negrito and Non-negrito languages. This study employs an ergative-absolutive framework. The initial result shows that the pronominal systems of the Southern Alta language consist of absolutive, ergative, oblique, and genitive pronouns. The ergative-absolutive framework unravels the morphosyntax of the pronominal system of Southern Alta. The framework helps describe the functions and characteristic of the different sets of pronouns. The study also reveals linguistic phenomena such as inclusivity/exclusivity, first person dual pronouns, homomorphy, cliticization, hierarchy, person-deixis interface and portmanteau pronouns. In conclusion, the ergative-absolutive framework fits the morphosyntactic analysis of the Southern Alta language. This study also suggests to examine the clausal construction including the noun phrases (NPs) of Southern Alta. Copyright © 2017 Marvin Abreu